Sikap Muslim Terhadap Modernitas: Kasus Gerakan Khilafatul Muslimin di Lampung - Ilham Mundzir (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2013)
The relationship between Islam, or Muslim-societies, and modernity has always-become interesting issue to discuss. This-is partly because, as predicted in certain-theory of modernization, the role and-significance of religion in modern society-will decrease. Yet, the above claim is no-longer relevant to the current situation-where sociologically, religions has still-survived and has even increasingly-become societal needs. Islamic societies-have often utilized religious symbols in-order to fight against modernization and-its extended issues, including seculariza--tion, democracy, gender equality, and the-like. This article is an attempt to present-the current response of Muslim societies-to modernity. By way of case study, it-elaborates on the experience of the-Khilafatul Muslimin, a fundamentalist-Movement that uses religious teachings as-a soursce to create a new world order